Sr / li co-doped coating with functions of promoting bone and bone immune regulation and preparation method thereof
Patent Information
- Application Number
- CN202610891873.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-11-03
AI Technical Summary
The bioinertness of existing titanium alloy implant surfaces leads to low bone integration rates, especially in osteoporotic environments and under conditions of osteoporosis and diabetes, making it difficult to achieve rapid and stable bone integration. Furthermore, traditional coatings lack the function of vascular coupling for osteogenic formation, and existing technologies have failed to effectively address specific problems related to macrophage immune regulation.
By preparing a material coating on the surface of a titanium alloy implant, and by adopting a preparation method for the titanium alloy implant, a technical problem is solved, and the existing technical problem is solved. A Sr/Li co-doped coating is used to prepare a Sr/Li co-doped coating on the surface of titanium alloy, which promotes the transformation of macrophages from M1 type to M2 type, enhances bone integration rate and immune regulation.
It has achieved improved bone integration rate on the surface of titanium alloy implants under pathological conditions such as osteoporosis, promoted the transformation of macrophages from M1 to M2 types, reduced inflammatory response, enhanced the integration strength between implant and bone and angiogenesis, and improved the long-term retention of implants.
Smart Images

Figure CN123027633A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical device technology, specifically relating to an Sr / Li co-doped coating, its preparation method, and its application. Background Technology
[0002] Titanium and titanium alloys are widely used in dental implants and orthopedic implants due to their excellent mechanical properties and biocompatibility. However, two key issues remain in clinical practice: First, the bioinertness of the implant surface leads to low bone integration rates, especially under pathological conditions such as osteoporosis and diabetes, where traditional coatings struggle to achieve rapid and stable bone integration, resulting in poor bone integration. Second, existing coatings primarily act directly on osteoblasts (such as the Sr / Zn / Mg-doped micro-arc oxidation coating in publication CN 115305551A), lacking the function of vascular-coupled osteogenic function. Furthermore, they neglect the regulation of the early immune microenvironment in vivo, particularly macrophage polarization. Macrophages include M1 and M2 types; when M1 macrophages dominate, excessive inflammatory responses occur, inhibiting osteogenic formation and leading to an imbalance in the bone immune microenvironment.
[0003] Therefore, developing titanium alloy surface-modified coatings that combine high bone integration rate, immune regulation, and bone-promoting functions is a new strategy to improve the long-term retention of implants. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing Sr / Li co-doped coatings, which constructs Sr / Li-doped micro-arc oxidation coatings in situ in a one-step manner.
[0005] Another object of the present invention is to provide a Sr / Li co-doped coating obtained by the above preparation method, which can promote the transformation of macrophages from M1 macrophages to M2 macrophages (M1 macrophages are pro-inflammatory cells, and M2 macrophages are anti-inflammatory cells).
[0006] Another object of the present invention is to provide an implant.
[0007] The objective of this invention is achieved through the following technical solution.
[0008] A method for preparing a Sr / Li co-doped coating includes: placing a cathode and a substrate serving as an anode in an electrolyte, performing micro-arc oxidation under stirring conditions, rinsing, and drying to obtain an Sr / Li co-doped coating on the substrate, wherein the substrate is made of pure titanium or a titanium alloy, and the electrolyte includes: water, strontium salt, lithium salt, sodium β-glycerophosphate, and calcium acetate.
[0009] In the above technical solution, the power supply for micro-arc oxidation is set to constant voltage mode, with a forward voltage of 250~350V, a forward current of 1~3A, a frequency of 600~1000 Hz, and a duty cycle of 60~80%.
[0010] In the above technical solution, the micro-arc oxidation treatment time is 8~15 min.
[0011] In the above technical solution, the temperature of the electrolyte is less than 40°C, preferably 30~37°C.
[0012] In the above technical solution, the concentration of strontium in the electrolyte is 0.300~0.700 mol / L, the concentration of lithium is 0.100~0.300 mol / L, the concentration of sodium β-glycerophosphate is 0.0316~0.1582 mol / L, and the concentration of calcium acetate is 0.0316~0.1581 mol / L.
[0013] In the above technical solution, the distance between the anode and the cathode is 8 to 12 cm.
[0014] In the above technical solution, the strontium salt is strontium acetate or strontium nitrate; the lithium salt is one or a mixture of lithium chloride, lithium acetate and lithium carbonate.
[0015] The Sr / Li co-doped coating obtained by the above preparation method.
[0016] In the above technical solution, in the Sr / Li co-doped coating, the strontium (Sr) is 10.0~20.5 wt% and the lithium (Li) is 0.5~3.2 wt% by mass percentage.
[0017] In the above technical solution, the roughness Ra value of the Sr / Li co-doped coating is 0.4~0.6 μm, the water contact angle is 30~45°, and the bonding strength is 84~87 MPa.
[0018] An implant with a surface covered by an Sr / Li co-doped coating.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0020] This invention provides a one-step Sr / Li co-doped coating prepared via micro-arc oxidation. This Sr / Li co-doped coating exhibits good bone immunomodulatory activity, effectively promoting the adhesion of pre-osteoblasts, the proliferation of macrophages and pre-osteoblasts, the osteogenic differentiation of pre-osteoblasts, and the vascularization of human umbilical vein endothelial cells. In vitro, it can induce RAW264.7 cells to M2 polarization by activating the p38-MAPK pathway. In vivo, it can effectively promote the conversion of peri-implant RAW264.7 cells from M1 to M2 types, thereby promoting peri-implant bone regeneration and implant-bone integration, enhancing implant-bone integration strength. The preparation method of this invention is simple and convenient, and is applicable to dental implants, orthopedic internal fixation devices, and craniofacial prostheses. Attached Figure Description
[0021] Figure 1 Photographs of the first, second, third, fourth, and fifth test samples;
[0022] Figure 2 The microstructures of the first, second, third, fourth, and fifth test samples are shown.
[0023] Figure 3 EDS plot for the fourth test sample;
[0024] Figure 4 The results are for the detection of metal ion release, where (a) is the Sr ion release result and (b) is the Li ion release result.
[0025] Figure 5 The thicknesses of the MAO coating prepared in Example 1, the Sr-doped coating prepared in Example 2, the Li-doped coating prepared in Example 3, the Sr / Li co-doped coating prepared in Example 4, and the Sr / Zn / Mg-doped coating prepared in Example 5 are shown.
[0026] Figure 6 The results are from the surface roughness test.
[0027] Figure 7 The results are the water contact angle test results;
[0028] Figure 8 The results are for the test of bonding strength;
[0029] Figure 9 The cell proliferation results were obtained based on RAW264.7 cells;
[0030] Figure 10 The results of fluorescent staining for macrophage-specific markers;
[0031] Figure 11Microscopic appearance of HUVECs cells at 2h, 4h, 8h and 12h of culture time in the microvascular formation assay;
[0032] Figure 12 The numbers of cell bundle nodes and microvessel loops at 4 h of culture are used to detect microvascular formation in HUVECs cells. (a) represents the number of cell bundle nodes at 4 h of culture, and (b) represents the number of microvessel loops at 4 h of culture.
[0033] Figure 13 The numbers of cell bundle nodes and microvessel loops at 8 h of culture are used to detect microvascular formation in HUVECs cells. (a) represents the number of cell bundle nodes at 8 h of culture, and (b) represents the number of microvessel loops at 8 h of culture.
[0034] Figure 14 Results of IL-6 secretion, an inflammatory cytokine, on day 3 of macrophage culture;
[0035] Figure 15 Immunofluorescence staining results for MC3T3-E1 cells;
[0036] Figure 16 The results of cell nucleus counting in the MC3T3-E1 cell adhesion assay;
[0037] Figure 17 The results of cell proliferation obtained based on MC3T3-E1 cells;
[0038] Figure 18 Results of Alizarin Red staining analysis of cellular mineralized nodules;
[0039] Figure 19 The results are from an alkaline phosphatase activity test.
[0040] Figure 20 The number of nodules is represented by (a) the number of nodules stained with ALP and (b) the number of nodules stained with Alizarin Red.
[0041] Figure 21 The appearance of connective tissue after hematoxylin-eosin staining;
[0042] Figure 22 The results are shown after hematoxylin-eosin staining, where (a) represents the membrane thickness and (b) represents the number of inflammatory cells;
[0043] Figure 23 The results are for immunofluorescence staining of anti-iNOS antibody, immunofluorescence staining of anti-ARG1 antibody, and DAPI staining.
[0044] Figure 24 This is a dimensional drawing of a titanium screw;
[0045] Figure 25 This is the result for bone volume fraction;
[0046] Figure 26 Toluidine blue staining results of hard tissue sections 8 weeks after implantation of implant staples;
[0047] Figure 27 The results show the bone integration rate 8 weeks after implantation of the implant.
[0048] Figure 28 The results of MASSON staining of hard tissue sections 8 weeks after implantation of implant staples;
[0049] Figure 29 The results of the torsion torque test for the implant screw twisting out of the tibia 8 weeks after implantation;
[0050] Figure 30 Heatmap of differentially expressed genes based on RNA sequence clustering;
[0051] Figure 31 The results of KEGG pathway enrichment analysis;
[0052] Figure 32 These are the results of a Western blot test. Detailed Implementation
[0053] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0054] The pure titanium sheet is a TA2 disc with a diameter of 10mm and a thickness of 0.5mm (No. 2 industrial pure titanium, atomic number 22, electron configuration of 3d24s2, relative atomic mass 47.87). The pure titanium sheet is polished and cleaned with sandpaper before use.
[0055] In the following embodiments, the cathode has the following dimensions: length 10cm, width 2cm, and height 2cm.
[0056] In the examples described below, the complete culture medium was prepared by uniformly mixing α-MEM and fetal bovine serum, wherein α-MEM accounted for 90 wt% and fetal bovine serum accounted for 10 wt% of the complete culture medium. Both α-MEM and fetal bovine serum were purchased from BI Company.
[0057] Example 1 (for comparison)
[0058] A method for preparing a MAO coating (hereinafter referred to as MAO) includes: placing a cathode (a stainless steel block (GB122092)) and a substrate as an anode in an electrolyte at a temperature of 35±2℃, performing micro-arc oxidation treatment for 10 min under stirring of the electrolyte, rinsing with deionized water after the micro-arc oxidation treatment, and drying at room temperature for 24 h to obtain a MAO coating on the substrate. The substrate is a pure titanium sheet, and the electrolyte is a mixture of deionized water, anhydrous sodium β-glycerophosphate, and calcium acetate. In the electrolyte of Example 1, the concentration of anhydrous sodium β-glycerophosphate is 0.0316 mol / L, the concentration of calcium acetate is 0.1581 mol / L, the power supply for the micro-arc oxidation treatment is set to constant voltage mode, the forward voltage is 300 V, the forward current is 3 A, the frequency is 800 Hz, the duty cycle is 80%, and the distance between the anode and the cathode is 8 cm.
[0059] Example 2 (for comparison)
[0060] A method for preparing an Sr-doped coating (Sr for short) is basically the same as in Example 1, except that the electrolyte is different. The electrolyte in Example 2 is a mixture of deionized water, strontium acetate, calcium acetate, and anhydrous sodium β-glycerophosphate. In the electrolyte of Example 2, the concentration of strontium acetate is 0.601 mol / L, the concentration of anhydrous sodium β-glycerophosphate is 0.0316 mol / L, and the concentration of calcium acetate is 0.1581 mol / L.
[0061] In this embodiment, an Sr-doped coating is obtained on a substrate, and the Sr content in the Sr-doped coating is 16.85 wt%.
[0062] Example 3 (for comparison)
[0063] A method for preparing a Li-doped coating (hereinafter referred to as Li) is basically the same as that in Example 1, except that the electrolyte is different. The electrolyte in Example 3 is a mixture of deionized water, lithium chloride, calcium acetate, and anhydrous sodium β-glycerophosphate. In the electrolyte of Example 3, the concentration of lithium chloride is 0.144 mol / L, the concentration of anhydrous sodium β-glycerophosphate is 0.0316 mol / L, and the concentration of calcium acetate is 0.1581 mol / L.
[0064] In this embodiment, a Li-doped coating is obtained on a substrate, wherein the Li content in the Li-doped coating is 1.5 wt%.
[0065] Example 4
[0066] A method for preparing a Sr / Li co-doped coating (hereinafter referred to as Sr / Li) includes: placing a cathode (a stainless steel block (GB122092)) and a substrate as an anode in an electrolyte at a temperature of 35±2℃, and performing micro-arc oxidation treatment under stirring of the electrolyte for 10 minutes. After the micro-arc oxidation treatment was completed, the substrate was rinsed with deionized water and dried at room temperature for 24 hours to obtain a Sr / Li co-doped coating on the substrate. The substrate was a pure titanium sheet, and the electrolyte was a mixture of deionized water, strontium salt (strontium acetate), lithium salt (lithium chloride), anhydrous sodium β-glycerophosphate, and calcium acetate (basic electrolyte). In the electrolyte of Example 4, the concentration of strontium was 0.601 mol / L, the concentration of lithium was 0.144 mol / L, the concentration of anhydrous sodium β-glycerophosphate was 0.0316 mol / L, and the concentration of calcium acetate was 0.1581 mol / L. The power supply for the micro-arc oxidation treatment was set to constant voltage mode, with a forward voltage of 300 V, a forward current of 3 A, a frequency of 800 Hz, a duty cycle of 80%, and a distance of 8 cm between the anode and cathode.
[0067] In the Sr / Li co-doped coating, the strontium (Sr) content is 13.61 wt% and the lithium (Li) content is 1.31 wt% by mass.
[0068] Example 5 (for comparison)
[0069] A method for preparing a Sr / Zn / Mg doped coating (hereinafter referred to as Sr / Zn / Mg) is basically the same as that in Example 1, except that the electrolyte is different. The electrolyte in Example 5 is a mixture of deionized water, strontium acetate, zinc acetate, magnesium chloride, calcium acetate, and anhydrous sodium β-glycerophosphate. In the electrolyte of Example 5, the concentration of strontium acetate is 0.601 mol / L, the concentration of zinc acetate is 0.06 mol / L, the concentration of magnesium chloride is 0.10 mol / L, the concentration of anhydrous sodium β-glycerophosphate is 0.0316 mol / L, and the concentration of calcium acetate is 0.1581 mol / L.
[0070] The thickness of the coatings was measured using a coating thickness gauge (LS225, Linshang Technology, Shenzhen, China). The coatings were one of the following: the MAO coating formed in Example 1, the Sr-doped coating formed in Example 2, the Li-doped coating formed in Example 3, the Sr / Li co-doped coating formed in Example 4, and the Sr / Zn / Mg-doped coating formed in Example 5. The results are as follows: Figure 5 As shown. By Figure 5It can be seen that the thicknesses of the MAO coating formed in Example 1, the Sr-doped coating formed in Example 2, the Li-doped coating formed in Example 3, the Sr / Li co-doped coating formed in Example 4, and the Sr / Zn / Mg-doped coating formed in Example 5 are 5.12, 14.21, 5.10, 13.51, and 9.65 μm, respectively.
[0071] The substrate and the MAO coating covering it in Example 1 were used as the first test sample, the substrate and the Sr-doped coating covering it in Example 2 were used as the second test sample, the substrate and the Li-doped coating covering it in Example 3 were used as the third test sample, the substrate and the Sr / Li co-doped coating covering it in Example 4 were used as the fourth test sample, and the substrate and the Sr / Zn / Mg-doped coating covering it in Example 5 were used as the fifth test sample.
[0072] Photos of the first, second, third, fourth, and fifth test samples are shown below. Figure 1 As shown.
[0073] The surface microstructure of the samples was observed using a Zeiss GEMINI 450 field emission scanning electron microscope (SEM). Microscopic images were acquired at different magnifications (×500, ×1000, ×2000, ×5000), and the results are as follows: Figure 2 As shown. The sample is one of the following: test sample 1, test sample 2, test sample 3, test sample 4, and test sample 5. Figure 2 It can be seen that the surface microstructure of each sample is regular, forming micropores of varying sizes, with shapes that are approximately circular or crater-like; the micropores are relatively uniformly distributed. Analysis of the fourth test sample using ImageJ software revealed micropore diameters ranging from 0.5 to 5 μm.
[0074] The first, second, third, and fourth test samples were analyzed using an energy dispersive spectroscopy (EDS) instrument on a Zeiss GEMINI 450 field emission electron scanning microscope. The results of the surface chemical element content are shown in Table 1. Based on the fourth test sample, the following was obtained: Figure 3 The EDS plot shown is composed of Figure 3 It can be seen that Ti, O, P, Ca, Sr, and Li elements are uniformly distributed in the Sr / Li co-doped coating.
[0075] Table 1
[0076]
[0077] The stability of Sr and Li doping is crucial for the long-term effectiveness of implant surfaces. If the implant surface cannot release these important signaling elements into the surrounding environment, the implant's effectiveness will be reduced. Metal ion release was detected in the leachate obtained from samples soaked for D days using inductively coupled plasma atomic emission spectrometry (ICP-AES, ICAP 6300, Thermo Fisher Scientific Co, USA). The samples were immersed in a glass containing 10 ml of PBS (pH = 7.4) and incubated at 37°C for D days with stirring to allow metal ion leaching. On day D, the sample and liquid were completely removed from the glass. The liquid in the glass was filtered to obtain the leachate, which was then used for metal ion release detection. D = 1, 4, 7, 14, or 30. The sample was one of the first, second, third, or fourth test samples. Sr ion release (e.g., ...) was obtained based on each sample. Figure 4 As shown in (a), the vertical axis is in μg / ml) and the Li ion release results (as shown in Figure 1). Figure 4 As shown in (b), the unit of the vertical axis is μg / L. Figure 4 It can be seen that the ion release rate slows down significantly starting from D=7, and gradually enters a plateau phase starting from D=14. These results indicate that Sr... 2+ and Li + The release can last for up to 30 days and is relatively stable. Figure 4 As shown in (a), the release level of strontium ions in the Sr / Li co-doped coating is lower than that in the Sr-doped coating, indicating that the introduction of lithium can suppress the dissolution of strontium ions. Figure 4 (b) shows that the incorporation of strontium also reduces the concentration of lithium ions released. Compared with the mono-doped system, the release curves of the two ions in the co-doped coating are flatter, with no obvious burst release, and they maintain a stable release trend with prolonged immersion time, demonstrating the advantage of long-term sustained release.
[0078] The surface roughness of the coating on the samples was tested using a roughness measuring instrument. The roughness measuring instrument used in this invention is a Germany DMG expert3D. Each sample was tested three times, and the average value was taken. The sample was one of the following: first test sample, second test sample, third test sample, fourth test sample, and fifth test sample. The test results are as follows: Figure 6 As shown. By Figure 6 It can be seen that the roughness of the coating in the first, second, third, fourth, and fifth test samples are 0.413, 0.477, 0.447, 0.477, and 0.434 μm, respectively. A rougher surface is more conducive to the growth of osteoblasts and angiocytes.
[0079] The water contact angle of the coated side of the sample was measured using a pendant drop contact angle meter (Germany Dataphysics OCA40 Micro). Three specimens were prepared for each sample, and the measurement was repeated three times for each specimen. The average value was taken as the test result. The sample was one of the first, second, third, fourth, and fifth test samples. The test results are as follows: Figure 7 As shown. By Figure 7 It can be seen that after micro-arc oxidation treatment, the water contact angles of the coatings in the first, second, third, fourth and fifth test samples are 43.13°, 37.9°, 42.0°, 42.9° and 41.9°, respectively.
[0080] The coating side of the samples was scratched using an automated scratch tester (Micro / nano-Scratcher-200 NE, Hu Huang Lab, Jilin University, China) to measure the bonding strength. The scratch test was conducted according to the guidelines of Zheng T X, Yang NY, Deng JP, et al. Multifunctional Sr / Zn-doped TiO2 micro / nanoporous coating enhances osseointegration by modulating signaling crosstalk of bone-related cells[J]. Chemical Engineering Journal, 2025, 511:161734. One of the following test samples was used: the first test sample, the second test sample, the third test sample, the fourth test sample, and the fifth test sample. The results are as follows: Figure 8 As shown, the bonding strengths of the first, second, third, fourth, and fifth test samples are 86.0436, 86.7506, 84.8734, 85.8239, and 84.8002 MPa, respectively.
[0081] Test cell proliferation optical density:
[0082] (1) Preparation before testing: Use a 24-well cell culture plate, place one autoclaved sample in each well, and set up 3 parallel samples for each sample. The average value is used as the test result. The sample is one of the first test sample, the second test sample, the third test sample, the fourth test sample, and the fifth test sample.
[0083] (2) Testing cell proliferation optical density: First, digest the cells. After centrifugation, take 10 μl of the cell count in a counting chamber, dilute with complete culture medium, and repeatedly pipette to mix evenly to prepare 1×10⁻⁶ cells / mL. 4 Cell suspension was prepared at 1, 3, 5, or 7 cells / mL. The cell suspension was seeded onto the sample surface (the coated side, 2 ml per well) and cultured in complete culture medium. On day T, the 24-well cell culture plate was removed, and the cell proliferation optical density was measured using a CCK-8 assay kit (Shanghai Beyotime Biotechnology Co., Ltd., C0037). Following the CCK-8 kit instructions, the cells were incubated at 37°C in the dark for 4 hours to obtain the test solution. 100 μL of the test solution from each well was transferred to a 96-well cell culture plate, and the absorbance (optical density, OD value) was measured at 450 nm using a microplate reader. The results were recorded. For T=1, 3, 5, or 7, the cells were macrophages (RAW264.7 cells, purchased from the Shanghai Institute of Cell Bank, Chinese Academy of Sciences) or pre-osteoblasts (MC3T3-E1 cells, purchased from the Shanghai Institute of Cell Bank, Chinese Academy of Sciences). When the cells were macrophages, the results were as follows. Figure 9 As shown. When the cells are pre-osteoblasts, the results are as follows. Figure 17 As shown.
[0084] Depend on Figure 9 (The vertical axis represents the OD value, i.e., the optical density of cell proliferation.) It can be seen that Examples 1-5 all significantly promoted macrophage proliferation, and the proliferative activity of macrophages increased with time. Examples 2-4 showed better results than Example 1, suggesting that Sr and Li have the effect of promoting macrophage proliferation. On days 1, 3, 5, and 7 of culture, the Sr / Li co-doped coating prepared in Example 4 showed the best effect in promoting macrophage proliferation.
[0085] Depend on Figure 17 (The vertical axis represents the OD value.) As can be seen, the OD values of Example 4 at each time point were significantly higher than those of Examples 1-3 and Example 5, indicating that Sr and Li elements have a synergistic effect in promoting the proliferation of pre-osteoblasts, and the combined application of Sr and Li is superior to their individual application. The promoting effect of Sr and Li on the proliferation of pre-osteoblasts is beneficial to peri-implant bone regeneration, thereby promoting implant osseointegration.
[0086] Macrophage-specific marker fluorescent staining:
[0087] Macrophages (MФ) have two subtypes, M1 and M2. M1 macrophages highly express inducible nitric oxide synthase (iNOS), while M2 macrophages highly express arginase 1 (ARG1). This invention uses immunofluorescence staining to detect the surface markers iNOS and ARG1 of M1 and M2 macrophages to evaluate the effects of different samples on MФ polarization. Specifically, the process involves: autoclaving samples (one of the first, second, third, fourth, and fifth test samples, with three replicates for each sample), wetting the sterilized samples with complete culture medium, and placing them in 24-well cell culture plates. The cell suspension (prepared by digesting macrophages, centrifuging, counting cells in a counting chamber with 10 μl, diluting with complete culture medium, and repeatedly pipetting to prepare a concentration of 1×10⁻⁶) is then prepared. 4Cell suspension at 2 mL / mL was seeded onto the coated side of each sample in a 24-well cell culture plate (2 mL of cell suspension per well). The plates were incubated at 37°C in a 5% CO2 incubator. On day 2, the liquid in the 24-well cell culture plate was aspirated. Each well was washed twice with PBS, and 1 mL of 4% paraformaldehyde solution was added to each well for fixation at room temperature for 1 hour. The plates were then washed twice with PBS and aspirated. Each well was blocked with PBS containing 1% BSA for 1 hour (i.e., the plate was filled with PBS containing 1% BSA and soaked for 1 hour). The PBS containing 1% BSA solution was discarded, and 30 mL of mixed primary antibody dilution was added to each well. (The method for obtaining the mixed primary antibody dilution involves mixing PBS and anti-iNOS antibody (anti-iNOS antibody purchased from Abcam)). The company, product ab15323 (by volume, the ratio of anti-iNOS antibody to PBS here is 1:50), obtained the iNOS primary antibody dilution; PBS and anti-ARG1 antibody (anti-ARG1 antibody purchased from Abcam, product ab215843, by volume, the ratio of anti-ARG1 antibody to PBS here is 1:50) were mixed to obtain the ARG1 primary antibody dilution. The iNOS primary antibody dilution and ARG1 primary antibody dilution were mixed in equal volumes to obtain the mixed primary antibody dilution. The mixture was incubated at 4°C for 12 hours. Residual liquid was aspirated, and the mixture was washed twice with PBS and aspirated. Then, 50 ml of fluorescent secondary antibody mixed working solution was added to each well (the method for obtaining the fluorescent secondary antibody mixed working solution includes: mixing PBS and Alexa Fluor® 488 labeled goat anti-mouse antibody (Alexa Fluor® 488 labeled goat anti-mouse antibody purchased from Abcam, product ab150113, by volume, the ratio of anti-ARG1 antibody to PBS here is 1:50) to obtain the iNOS primary antibody dilution; PBS and anti-ARG1 antibody (anti-ARG1 antibody purchased from Abcam, product ab215843, by volume, the ratio of anti-ARG1 antibody to PBS here is 1:50) to obtain the ARG1 primary antibody dilution; the iNOS primary antibody dilution and ARG1 primary antibody dilution were mixed in equal volumes to obtain the mixed primary antibody dilution); the mixture was incubated at 4°C for 12 hours. Residual liquid was aspirated, and the mixture was washed twice with PBS and aspirated; then 50 ml of fluorescent secondary antibody mixed working solution was added to each well (the method for obtaining the fluorescent secondary antibody mixed working solution includes: mixing PBS and Alexa Fluor® 488 labeled goat anti-mouse antibody (Alexa Fluor® 488 labeled goat anti The ratio of Fluor®488-labeled goat anti-mouse antibody to PBS was 1:200 to obtain Alexa Fluor®488-labeled goat anti-mouse secondary antibody dilution. PBS and Cy3-labeled goat anti-rabbit antibody (purchased from Abcam, model ab97075, volume ratio of Cy3-labeled goat anti-rabbit antibody to PBS was 1:200) were mixed to obtain Cy3-labeled goat anti-rabbit secondary antibody dilution. Equal volumes of Alexa Fluor®488-labeled goat anti-mouse secondary antibody dilution and Cy3-labeled goat anti-rabbit secondary antibody dilution were mixed to prepare a fluorescent secondary antibody mixed working solution. The solution was incubated at room temperature for 1.5 hours. After washing twice with PBS, 30 ml of DAPI staining solution was added (DAPI staining agent purchased from Abcam was diluted with PBS at a ratio of 1:10 to obtain DAPI staining solution) and stained for 5 minutes. The expression of iNOS and ARG1 was observed under a fluorescence microscope. Images were taken from randomly selected fields of view, and the average fluorescence intensity was quantitatively analyzed using ImageJ software. Results are as follows: Figure 10 As shown.
[0088] Figure 10 Immunofluorescence staining results of M1 macrophage surface markers (iNOS) and M2 macrophage surface markers (ARG1) were performed on RAW264.7 cells (macrophages) after culturing for 2 days. Merge represents the fluorescence overlay pattern. Figure 10 It was found that in Example 4, the expression of the surface marker ARG1 on M2 macrophages was the strongest, significantly stronger than in Examples 1-3 and Example 5; while in Example 4, the expression of the surface marker iNOS on M1 macrophages was the weakest, significantly lower than in Examples 1-3. M1 macrophages are pro-inflammatory, secreting inflammatory factors such as IL-1, IL-6, and TNFα, which exacerbate the inflammatory response; while M2 macrophages are anti-inflammatory, secreting anti-inflammatory factors such as IL-4 and IL-10, promoting inflammation recovery and accelerating tissue regeneration. These results indicate that the Sr / Li co-doped coating in Example 4 can induce macrophage transformation from M1 to M2, thereby reducing inflammation and promoting tissue regeneration and repair.
[0089] Microvascular formation detection of HUVECs (human umbilical vein blood endothelial cells, purchased from Science): The detection was performed according to the method described in publication CN 115305551A, "Detection of Microvascular Formation of HUVECs on Coated Surfaces". One of the following four test samples was used: the first test sample, the second test sample, the third test sample, and the fourth test sample. The results are as follows: Figures 11-13 As shown, where, Figure 11 Microscopic appearance at 2h, 4h, 8h and 12h of culture; Figure 12 The number of cell bundle nodes at 4 hours of culture (i.e. Figure 12 The number of nodes and the number of microvascular loops (i.e., the number of nodes) Figure 12 (Middle "microvascular count"); Figure 13 The number of cell bundle nodes and microvascular loops at 8 hours of culture.
[0090] Depend on Figures 11-13 It can be seen that at the 4th and 8th hour of culture, the number of microvascular loops and cell bundle nodes in Example 4 were higher than those in Examples 1-3, and the differences were statistically significant. The above results indicate that the Sr and Li elements in Example 4 can synergistically promote microvascular formation, and the combined application of the two has a better effect.
[0091] Detection of the inflammatory factor IL-6: A 24-well cell culture plate was used, with one autoclaved sample (either the first or fourth test sample) placed in each well, and three replicates per sample. 2 ml of RAW264.7 cell suspension was aspirated from each well (the method for obtaining RAW264.7 cell suspension includes: digesting RAW264.7 cells, centrifuging, taking 10 μl for cell counting in a counting chamber, diluting with complete culture medium, and repeatedly pipetting to prepare 1×10⁻⁶ cells / well). 4 RAW264.7 cell suspension (number of cells / mL) was seeded onto the sample surface (the coated side). On day 3, the liquid in the 24-well cell culture plate was removed, centrifuged, and the supernatant was collected. The IL-6 secretion level in the supernatant was detected using an ELISA kit (Jianglai Biotechnology, Shanghai) according to the instructions. The results are as follows: Figure 14 As shown, the macrophages in Example 4 secreted IL-6 significantly less than those in Example 1, indicating that the Sr and Li elements in Example 4 can significantly reduce the secretion of the macrophage inflammatory factor IL-6, thereby alleviating inflammation in the local bone microenvironment and promoting bone tissue regeneration and repair.
[0092] MC3T3-E1 cell adhesion assay:
[0093] (1) Pre-experiment preparation: Use 24-well cell culture plates, and place one autoclaved sample (one of the first, second, third, and fourth test samples) in each well. Set up three parallel samples for each sample and calculate the average value. Prepare cell suspension: First, digest MC3T3-E1 cells. After centrifugation, take 10 μl in a counting chamber for cell counting, dilute with complete culture medium, and repeatedly pipette to prepare 1×10⁻⁶ cells / well. 4 Cell suspension of cells / mL.
[0094] (2) Cell adhesion detection: Cell suspension was evenly seeded onto the coated side of each sample in a 24-well cell culture plate (2 mL of cell suspension per well), and incubated in a 37°C, 5% CO2 cell culture incubator for 72 h. The liquid in the 24-well cell culture plate was aspirated, and each well was rinsed 3 times with 1 mL of PBS and then aspirated. 1 mL of 4% paraformaldehyde solution was added to each well, and the plate was fixed at room temperature for 30 min. After rinsing 3 times with PBS, the solution was discarded. 1 mL of 0.5% Triton X-100 was added to each well and allowed to stand for 20 min to allow cell perforation. After rinsing 3 times with PBS, the solution was aspirated. 2 mL of DAPI staining solution (DAPI staining agent purchased from Abcam was diluted with PBS at a ratio of 1:10 to obtain DAPI staining solution) and 1 mL of 10 μg / mL phalloidin staining agent (purchased from Sigma, USA) were added to each well and incubated in a 37°C, 5% CO2 cell culture incubator for 15 min. The cells were observed under a fluorescence microscope (images acquired at 20X), and cell nuclei were counted using Image-Pro Plus software. The average value was taken as the number of adherent cells. Results are as follows: Figure 15 and Figure 16 As shown, where, Figure 15 Immunofluorescence staining results of pre-osteoblasts (MC3T3-E1 cells) after culturing on the coating surfaces of different samples for 72 h: First row: Phalloidin staining of the cytoskeleton; Second row: DAPI staining of the cell nucleus; Third row: Fluorescence overlay (Merge). Figure 16 The result is the count of cell nuclei.
[0095] Depend on Figure 16 It can be seen that the cell adhesion number corresponding to Example 4 is significantly higher than that of Examples 1-3, and the cell adhesion number from largest to smallest is: Example 4 > Example 2 > Example 3 > Example 1. This suggests that the Sr / Li co-doped coating of Example 4 can better promote early osteoblast adhesion, with Sr having a stronger effect than Li, and the combined application of the two has a synergistic enhancement effect. Cell adhesion is a prerequisite for the formation of bone bond, and the surface state of the material determines the adhesion of osteoblasts. The Sr and Li elements on the coating are beneficial to promoting the cell adhesion of pre-osteoblasts on the coating. In addition, the surface roughness and hydrophilicity of the coating also affect the effect of cell adhesion on the coating surface. The above factors together make the Sr / Li co-doped coating have better cell adhesion.
[0096] Alkaline phosphatase (ALP) is an important marker of osteoblast maturation and bone formation capacity. The method for testing ALP activity is as follows: A 24-well cell culture plate is used, with one autoclaved sample placed in each well. Each sample group is tested in triplicate, and the ALP activity is calculated as an average. The sample used is one of the following five test samples: the first, second, third, fourth, and fifth test samples. The aforementioned "cell proliferation optical density" is 1×10⁻⁶. 4 Cell suspension (based on MC3T3-E1 cells) was seeded onto the surface of each sample at 1 mL per well. The cells were then transferred to a 37°C 5% CO2 cell culture incubator and cultured in complete medium. After 24 hours of cell adhesion, the complete medium was replaced with complete medium containing osteogenic induction solution (prepared from dexamethasone, anhydrous β-glycerophosphate, and ascorbic acid; the complete medium containing osteogenic induction solution contained 100 nmol / L dexamethasone, 10 mmol / L anhydrous β-glycerophosphate, and 50 mg / L ascorbic acid). The complete medium containing osteogenic induction solution was then replaced every 2 days. On day 7 of culture in the complete medium containing osteogenic induction solution, the 24-well cell culture plates were removed, gently washed twice with PBS, and aspirated. Staining was performed using an alkaline phosphatase staining kit from Nanjing Jiancheng Biotechnology Institute. The staining results are shown in [Figure 1]. Figure 19 .
[0097] Alizarin red staining analysis of cellular mineralized nodules: This method is essentially the same as the "Method for Testing Alkaline Phosphatase Activity," with the only difference being the culture time in complete medium containing osteogenic induction solution and the staining kit. For alizarin red staining analysis of cellular mineralized nodules, cells were cultured in complete medium containing osteogenic induction solution for 14 days. The 24-well cell culture plates were then removed, gently washed twice with PBS, and aspirated. Staining was performed using an alizarin red staining kit (Nanjing Jiancheng Bioengineering Institute, operated according to the instructions) to analyze the formation of mineralized nodules. Results are as follows: Figure 18 As shown.
[0098] The number of ALP-stained nodules was determined based on alkaline phosphatase activity assays, such as... Figure 20 As shown in (a), the number of alizarin red stained nodules was obtained based on the alizarin red mineralized nodule staining analysis, as follows: Figure 20As shown in (b). The results showed that the trend of Alizarin Red staining and ALP staining was the same, with the number of stained nodules in Example 4 being greater than that in Example 5. The Sr / Li co-doped coating prepared in Example 4 had the strongest effect, and the Sr / Li co-doped coating had a stronger osteogenic capacity than the Sr / Zn / Mg doped coating. The above results indicate that both Sr and Li elements in Example 4 have the effect of promoting osteoblast differentiation and maturation, and their effects are synergistically enhanced. Pre-osteoblast osteogenic differentiation to produce ALP and collagen mineralization to form mineralized nodules are key steps in bone formation, suggesting that Sr and Li elements in Example 4 can promote the differentiation and maturation of pre-osteoblasts, enhance bone mineralization deposition on the implant surface, and thus promote implant-bone integration.
[0099] Implant implantation experiment
[0100] Prepare the first type of implant nail: It is basically the same as in Example 1, except that "the substrate is a pure titanium sheet" is replaced with "the substrate is a titanium screw".
[0101] Prepare a second type of implant: It is basically the same as in Example 2, except that "the substrate is a pure titanium sheet" is replaced with "the substrate is a titanium screw".
[0102] Prepare a third type of implant: It is basically the same as in Example 3, except that "the substrate is a pure titanium sheet" is replaced with "the substrate is a titanium screw".
[0103] Prepare the fourth type of implant: It is basically the same as in Example 4, except that "the substrate is a pure titanium sheet" is replaced with "the substrate is a titanium screw".
[0104] Rat implantation surgery: Forty SD rats (3-month-old male Sprague-Dawley SD rats weighing 220±22.58g, provided by the Experimental Animal Center of North China University of Technology, quality certificate number Huafukang SCXK (Beijing) 2014-004) were selected. Anesthesia was achieved by intraperitoneal injection of 3ml of 3% sodium pentobarbital solution (purchased from Sigma). The left tibia of each SD rat was prepared, disinfected with iodine, and draped. A longitudinal incision was made near the metaphysis of the tibia, cutting through the skin, subcutaneous tissue, and muscle layer to fully expose the tibial bone surface. A 2mm diameter implant bur (the implant bur and titanium screw were the same size) was used. Figure 24 As shown, Figure 24Drilling was performed perpendicular to the bone plane using a medium-sized (unit: mm) hole, with copious amounts of 0.9% saline solution used for cooling and flushing during drilling. The drilling penetrated the medullary cavity and completely pierced the anterior and posterior cortical bone of the tibia, forming a tibial implant socket. Forty SD rats were then divided into four groups of ten rats each, with each group receiving the same type of implant. The implant consisted of an implant screw and an implant plate corresponding to the same embodiment. Specifically, one implant screw was implanted into the tibial implant socket of each SD rat, and one implant plate was implanted subcutaneously in the back. For three consecutive days post-surgery, 100,000 units of penicillin were injected intramuscularly daily to prevent wound infection. The implant screw was one of four types: Type 1, Type 2, Type 3, and Type 4. The implant plate was one of four test samples: Type 1, Type 2, Type 3, and Type 4.
[0105] Two weeks post-surgery, connective tissue surrounding the subcutaneous graft on the back (one of the first, second, third, and fourth test samples) was harvested. The connective tissue was stained using a hematoxylin-eosin (HE) staining kit (purchased from Beyotime Pharmaceuticals and used according to the instructions). The results are as follows: Figure 21 As shown, based on Figure 21 Measure the film thickness to obtain Figure 22 The membrane thickness shown in (a) is based on Figure 21 Perform capsule inflammatory cell count analysis to obtain Figure 22 The inflammatory cell count results are shown in (b). Figure 22 The results show that the coating thickness is in the order of Example 4 < Example 3 < Example 1 < Example 2. Example 4 has the smallest coating thickness, indicating that the Sr / Li co-doped coating in Example 4 causes the least foreign body immune reaction and has the best tissue compatibility. Figure 22 As shown in (b), the order of the number of inflammatory cells from largest to smallest is: Example 4 < Example 2 < Example 3 < Example 1. Example 4 has the fewest number of inflammatory cells, indicating that the Sr / Li co-doped coating prepared in Example 4 has the best biocompatibility, causes the mildest inflammatory response, and is more conducive to the formation of a microenvironment that promotes bone tissue regeneration.
[0106] Two weeks post-surgery, connective tissue surrounding the subcutaneous grafts (one of the first and fourth test samples) on the back was harvested. This connective tissue contained the M1 macrophage surface marker iNOS and the M2 macrophage surface marker ARG1. Immunofluorescence staining for M1 macrophage surface markers was performed using anti-iNOS antibody (purchased from Abcam, stained according to the instructions). Immunofluorescence staining for M2 macrophage surface markers was performed using anti-ARG1 antibody (purchased from Abcam, stained according to the instructions). The effect of the grafts on macrophage polarization was observed. Simultaneously, DAPI staining solution (DAPI staining agent purchased from Abcam was diluted 1:10 with PBS) was used to stain the cell nuclei, and the results were observed. (The results are as follows...) Figure 23 As shown. Figure 23 The results showed that the fluorescence intensity of the M2 macrophage surface marker ARG1 in Example 4 was significantly stronger than that in Example 1; while the fluorescence intensity of the M1 macrophage surface marker iNOS was significantly lower than that in Example 1. This result is consistent with... Figure 10 The in vitro results were similar. M1 macrophages are pro-inflammatory and can secrete inflammatory factors such as IL-6 and TNFα, which aggravate the inflammatory response; while M2 macrophages are anti-inflammatory and can secrete anti-inflammatory factors such as IL-4 and IL-10, which promote inflammation recovery and accelerate tissue regeneration. The above results indicate that the Sr / Li co-doped coating of Example 4 can induce macrophages to transform from M1 to M2, thereby reducing inflammation and promoting tissue regeneration and repair.
[0107] Figure 29 The results of the torsion torque test of the implant at week 8 after implantation were as follows: Wang Huan. Study on in vivo osteogenic and long-term antibacterial properties of Sr / Ag microporous coating implants [D]. North China University of Technology, 2020. DOI:10.27108 / d.cnki.ghelu.2020.000205. The results showed that the torsion torque values were Sr / Li>Sr>Li>MAO; Sr / Li had the highest torsion torque. The implant with Sr / Li co-doped coating could withstand greater mechanical torque, indicating that it was most firmly integrated with bone tissue and could withstand greater mechanical stimulation.
[0108] The SD rats were euthanized at week 8 and subjected to the following tests: Micro-CT scanning was performed. First, specimens were collected using Cruiser software. Three-dimensional image reconstruction was performed on the specimens (connective tissue surrounding the subcutaneous graft on the back was used as the specimen; the graft was one of the first, second, third, or fourth test samples). Then, image analysis was performed using Avatar software. A volume of interest (VOI) was defined on the reconstructed three-dimensional image (refer to Zheng TX, Yang NY, Deng JP, et al. Multifunctional Sr / Zn-doped TiO2 micro / nanoporous coating enhances soseointegration by modulating signaling crosstalk of bone-related cells[J]. Chemical Engineering Journal, 2025, 511: 161734.). Finally, ImageJ software was used to quantitatively calculate the bone volume fraction (BV / TV) (TV is the volume of the VOI, and BV is the volume of newly formed bone tissue within that VOI). The results are as follows: Figure 25 As shown.
[0109] Depend on Figure 25 It can be seen that the BV / TV corresponding to the Sr / Li co-doped coating is 0.62±0.05, which is significantly higher than that of the Sr-doped coating (0.57±0.11), the Li-doped coating (0.49±0.02), and the MAO coating (0.43±0.10). This indicates that Sr and Li elements can effectively promote peri-implant bone regeneration, and the two elements have a synergistic enhancing effect.
[0110] Eight weeks after implantation, bone tissue with the implant in the tibia was harvested as a specimen (the implant remained in the body and was prepared into a tissue section; the implant was one of four types: type 1, type 2, type 3, or type 4). The specimen with the implant was prepared into hard tissue sections and stained with toluidine blue (the toluidine blue kit was purchased from Beyotime Biotechnology Co., Ltd., and used according to the instructions). The results are as follows... Figure 26As shown, the results indicate that within the sensitive region (ROI) surrounding the implant (refer to Wang H, Zheng TX, Yang NY, Li Y, Sun H, Dong W, Feng LF, Deng JP, Qi MC. Osteogenic and long-term antibacterial properties of Sr / Ag-containing TiO2 microporous coating in vitro and in vivo. J Mater Chem B. 2023 Mar 30;11(13):2972-2988. doi: 10.1039 / d2tb01658c. PMID: 36919628. to determine the ROI), the fourth type of implant ( Figure 26 The surface of the Sr / Li group showed the most extensive bone tissue coverage. The bone integration rate was calculated using ImageJ software, and the results are as follows: Figure 27 As shown. The bone integration rate (IBCR) is: Sr / Li > Sr > Li > MAO; the fourth type of implant has a bone integration rate as high as 98.35%, which is higher than that of the first type of implant ( Figure 27 The content of "MAO" in the implant increased by 21.03% from 77.32%; this indicates that Sr and Li elements can effectively promote osseointegration of implants, thereby improving the mechanical properties of implants and increasing their long-term success rate.
[0111] Eight weeks after implantation, bone tissue with the implant in the tibia was harvested as a specimen (the implant remained in the body and was prepared into a tissue section; the implant was one of four types: type 1, type 2, type 3, or type 4). The specimen with the implant was prepared into hard tissue sections and stained with MASSON (the MASSON staining kit was purchased from Beyotime Biotechnology and used according to the instructions). The results are as follows: Figure 28 As shown; the results indicate that the fourth type of implant ( Figure 28 The trabeculae around the implant (Sr / Li) were the most abundant and densest, with the number of trabeculae being Sr / Li > Sr > Li > MAO; this indicates that Sr and Li elements can effectively promote peri-implant bone regeneration, and the two elements have a synergistic enhancing effect.
[0112] Mechanism verification
[0113] A 24-well cell culture plate was used, with one autoclaved sample (either the first or fourth test sample) placed in each well. RAW264.7 cell suspension was prepared by digesting the cells, centrifuging, and then counting the cells in a counting chamber with 10 μl of the suspension. The suspension was then diluted with complete culture medium, and the cells were repeatedly pipetted to prepare a 1×10⁻⁶ plate. 4 RAW264.7 cell suspension (2 ml / mL) was seeded onto the sample surface (coated side, 2 ml / well) and cultured in a 37°C, 5% CO2 cell incubator. On day 3, the liquid in the 24-well cell culture plate was discarded, and 1 ml of TRIzol was added to each well to lyse the cells. The lysate was collected and transferred to 1.5 mL centrifuge tubes and sent to Biomarker Biotech for RNA sequence detection. Figure 30 The RNA sequence differentially expressed gene clustering heatmap shown is denoted as the MAO coating group based on the results obtained from the first test sample, and as the Sr / Li coating group based on the results obtained from the fourth test sample. Figure 30 In the table, "MAO1", "MAO2", and "MAO3" represent three replicates from the MAO-coated group, and "Sr-Li1", "Sr-Li2", and "Sr-Li3" represent three replicates from the Sr / Li-coated group. The results showed significant differential gene expression between the Sr / Li-coated group and the MAO-coated group. Specifically, 228 differentially expressed genes were identified in the Sr / Li-coated group; compared to the MAO-coated group, 79 genes showed increased expression levels (upregulation), and 149 genes showed decreased expression levels (downregulation), significantly altering the gene expression profile of peri-implant cells and confirming its ability to actively regulate bone metabolism homeostasis. Further functional classification of differentially expressed genes revealed that upregulated genes were mainly enriched in cytoskeleton tissues (e.g., Fhod3, Ajuba), Wnt signaling pathways (e.g., Frat2, Cyp27b1), and myeloid cell immune responses (e.g., Cd33, Ccr1, Fcgr3). Downregulated genes were broadly involved in interferon-induced antiviral immune responses (e.g., Ifit1 / 2 / 3, Isg15, Rsad2, Mx2), chemokines and inflammatory mediators (e.g., Ccl22, Cx3cl1, Il6), and antigen processing and presentation (e.g., H2-Eb1, Tap1). This up / down regulation pattern suggests that the Sr / Li co-doped coating promotes bone repair by activating osteogenic and angiogenesis-related genes, and reduces bone resorption by inhibiting inflammation-related genes and osteoclast-related factors, thereby creating a positive osteogenic microenvironment.
[0114] KEGG is a database used for systematic analysis of gene function and genomic information. KEGG studies genes and their expression information as a holistic network. Differentially expressed genes after RNA sequencing were subjected to KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment analysis. The results are as follows: Figure 31 As shown. Figure 31 The results showed that, compared with the MAO coating group, the differentially expressed genes in RAW264.7 cells of the Sr / Li coating group were mainly enriched in the TNF signaling pathway, the cytokine-receptor interaction pathway, and the inflammation-related disease pathway. These signaling pathways are involved in the immune regulation of the bone microenvironment and tissue regeneration and repair.
[0115] A 24-well cell culture plate was used, with one autoclaved sample (either the first or fourth test sample) placed in each well, and three replicates per sample. RAW264.7 cell suspension was prepared (the method for obtaining RAW264.7 cell suspension includes: digesting RAW264.7 cells, centrifuging, taking 10 μl for cell counting in a counting chamber, diluting with complete culture medium, and repeatedly pipetting to prepare 1×10⁻⁶ cells / well). 4 RAW264.7 cell suspension (2 ml / mL) was seeded onto the sample surface (coated side, 2 ml per well) and cultured in a 37°C, 5% CO2 cell culture incubator. On day 3, the liquid in the 24-well cell culture plate was discarded, and 300 μL of LRIPA lysis buffer (purchased from Shanghai Beyotime Biotechnology Co., Ltd., P0013B) was added to each well. Lysis was performed on ice for 30 min, and the cell lysate was scraped off. The lysate was centrifuged at 12000 rpm and 4°C for 15 min, and the supernatant was collected to obtain RAW264.7 cell protein samples. RAW264.7 cell protein samples were collected for Western blot experiments (results based on the first test sample were designated as the MAO coating group, and results based on the fourth test sample were designated as the Sr / Li coating group) to detect the expression of P38-MAPK pathway proteins. The results are shown below. Figure 32 As shown, Figure 32In the text, "P38" refers to P38 protein kinase, "p-P38" refers to phosphorylated P38 protein kinase, and "GAPDH" is the cell's internal reference protein. The results showed that compared to the MAO coating group, the Sr / Li coating group significantly increased p-P38 expression levels while having no significant effect on P38 expression levels. This indicates that the Sr / Li co-doped coating can promote P38 protein kinase phosphorylation, suggesting that the P38-MAPK pathway is activated. Given that the activated P38-MAPK pathway is a key signaling axis driving macrophage polarization towards M2, this suggests that the Sr / Li co-doped coating can induce macrophage polarization towards M2 and regulate bone immunity by activating the MAPK pathway through P38 phosphorylation.
[0116] This invention combines the application of Sr with the application of Li to jointly promote angiogenesis. Sr and Li synergistically activate the P38-MAPK pathway, driving M2 polarization in macrophages. In contrast, existing technologies (such as the Sr / Zn / Mg micro-arc oxidation coating in publication CN 115305551A) directly act on osteoblasts, simply stimulating them directly and neglecting the crucial regulatory role of the immune microenvironment in bone regeneration. This approach fails to address the risks of bone resorption and implantation failure caused by early inflammatory responses.
[0117] This invention features a unique timing of action. The Sr / Li co-doped coating of this invention preferentially modulates the early (1-3d) immune microenvironment (through... Figure 10 The immunofluorescence assay results indicate that the coating reduces the secretion of inflammatory factors and creates a bone microenvironment conducive to tissue regeneration. It then affects osteoblast adhesion (2-3 days, characterized by MC3T3-E1 cell adhesion detection on the coating surface) and osteogenic differentiation (7 days, characterized by alkaline phosphatase activity assay). This, in turn, promotes mineral deposition on the coating surface (14 days, characterized by Alizarin Red mineralized nodule staining analysis). Ultimately, it enhances bone regeneration on the implant surface (8 weeks) (characterized by implant placement experiments), improving implant osseointegration and torsional torque; aligning with the new concept of "immune-first" bone repair.
[0118] To address the lack of vascular-coupled osteogenic function in existing technologies, this invention prepares a Sr / Li co-doped coating. The Sr / Li co-doped coating can reshape the bone immune microenvironment by regulating macrophage polarization towards the M2 type, thereby promoting vascular-coupled osteogenic formation and ultimately significantly improving the bone integration effect of implants under pathological conditions. The preparation method is simple, economical, and easy to mass-produce.
[0119] The present invention has been described above by way of example. It should be noted that any simple modifications, alterations or other equivalent substitutions that can be made by those skilled in the art without creative effort without departing from the core of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing a Sr / Li co-doped coating, characterized in that, include: The cathode and the substrate serving as the anode are placed in an electrolyte and subjected to micro-arc oxidation under stirring conditions. After rinsing and drying, an Sr / Li co-doped coating is obtained on the substrate. The substrate is made of pure titanium or a titanium alloy. The electrolyte includes water, strontium salt, lithium salt, sodium β-glycerophosphate, and calcium acetate.
2. The preparation method according to claim 1, characterized in that, The power supply for the micro-arc oxidation process is set to constant voltage mode, with a forward voltage of 250~350 V, a forward current of 1~3 A, a frequency of 600~1000 Hz, and a duty cycle of 60~80%.
3. The preparation method according to claim 1, characterized in that, The micro-arc oxidation treatment time is 8~15 min.
4. The preparation method according to claim 1, characterized in that, The temperature of the electrolyte is less than 40℃.
5. The preparation method according to claim 1, characterized in that, In the electrolyte, the concentrations of strontium are 0.300–0.700 mol / L, lithium are 0.100–0.300 mol / L, sodium β-glycerophosphate are 0.0316–0.1582 mol / L, and calcium acetate are 0.0316–0.1581 mol / L.
6. The preparation method according to claim 1, characterized in that, The distance between the anode and the cathode is 8–12 cm.
7. The preparation method according to claim 1, characterized in that, Strontium salts are strontium acetate or strontium nitrate; lithium salts are one or a mixture of lithium chloride, lithium acetate and lithium carbonate.
8. The Sr / Li co-doped coating obtained by the preparation method according to any one of claims 1 to 7.
9. The Sr / Li co-doped coating according to claim 8, characterized in that, In the Sr / Li co-doped coating, the strontium content is 10.0~20.5 wt% and the lithium content is 0.5~3.2 wt% by mass percentage.
10. An implant, characterized in that, Its surface is covered with the Sr / Li co-doped coating as described in claim 8.
Citation Information
Patent Citations
Micro-arc oxidation coating doped with Sr / Zn / Mg as well as preparation method and application of micro-arc oxidation coating
CN115305551A
